Optimization of the Halal Food Industry in Support of Increasing Local Revenue in South Sulawesi - Umar, Rahmawati; Siradjuddin, Siradjuddin (Indonesian Journal of Advanced Research, 2025)
The halal industry is one of the strategic sectors that has great potential in driving national economic growth, especially in countries with a Muslim majority population such as Indonesia. This article examines the urgency of developing the halal industry as an integral part of an inclusive and sustainable sharia economic ecosystem. The main focus is on the challenges and opportunities for developing the halal industry in Indonesia, including the role of regulation, business actor awareness, and halal certification mechanisms which are key elements in ensuring consumer trust. Through a descriptive qualitative approach and current literature studies, it was found that halal certification not only functions as a guarantee of product halalness, but also as a strategy to increase the competitiveness of MSMEs in the global market. The main obstacles in developing the halal industry include low halal literacy among MSMEs, limited access to information and certification costs, and suboptimal synergy between stakeholders. Therefore, an integrated policy strategy is needed between the government, certification institutions, and the education sector to encourage the birth of a highly competitive and global halal industry ecosystem. This research contributes to efforts to formulate data-based policies in the development of the national halal industry.